THU0503 Identification of optimal subcutaneous (SC) doses of tocilizumab in children with polyarticular-course juvenile idiopathic arthritis (PCJIA). (15th June 2017) - Benedetti, F De; Ruperto, N; Lovell, D; Ramanan, AV; Cuttica, R; Weiss, JE; Henrickson, M; Schmeling, H; Anton, J; Minden, K; Hsu, J; Bharucha, K; et al.
Abstract : Background: Efficacy and safety of intravenous (IV) tocilizumab (TCZ) have been shown in patients (pts) with pcJIA. 1 Objectives: Determine appropriate dosing regimens of SC TCZ in pcJIA. Methods: Pts were aged 1–17 y with pcJIA, inadequate response/intolerance to MTX and TCZ-naive or receiving TCZ IV with adequate disease control. TCZ SC was administered open label by body weight (BW)–based dosing modeled on IV dosing in pcJIA and SC dosing in adult rheumatoid arthritis: pcJIA pts <30kg received TCZ 162mg every 3 wks (Q3W) and pts ≥30kg received TCZ 162mg Q2W for 52 wks. Safety, efficacy (exploratory) and model-computed pharmacokinetic (PK) and pharmacodynamic (PD) parameters were assessed. Results: 52 pts were enrolled; 27 <30kg and 25 ≥30kg BW; 85% and 56% were TCZ naive. Since no notable difference in steady state PK occurred in naive vs non-naive pts, pooled data are shown. Median Cmin was similar between BW groups and higher than with TCZ IV (TCZ IV median Cmin : 3.2 μg/mL for 10mg/kg <30kg BW and 7.3 μg/mL for 8mg/kg ≥30kg BW) ensuring adequate exposure from SC doses. Median Cmax was lower from SC than IV dosing. Changes in PD parameters for TCZ-naive pts were consistent with those for TCZ IV. JADAS-71 generally improved (Table), with trends consistent with those for TCZ IV. Infections were the most frequent adverse event (AE), reported in 36 pts; 2 serious infections occurred in 1 pt. Injection site reactions occurred in 15% pts in the <30kg group and 44% pts in the ≥30kg group. The most common symptoms were erythema, swelling, hematoma, pain and pruritus. No serious hypersensitivity, AE leading to withdrawal, opportunistic infection, serious hepatic AE or death occurred. Overall there were 4 serious AEs in 3 pts (7.9/100 pt-y, consistent with that for TCZ IV). Conclusions: The BW-based TCZ SC dosing regimens for pcJIA provided adequate exposure to support efficacy comparable to that for TCZ IV, with an acceptable benefit-risk profile. References: Brunner HI et al. Ann Rheum Dis 2014;74:1110–7. Disclosure of Interest: F. De Benedetti Grant/research support from: Novartis, Roche, Pfizer, SOBI, AbbVie, Novimmune, BMS, Sanofi, N. Ruperto Consultant for: AbbVie, Amgen, Alter, AstraZeneca, Baxalta Biosimilars, Biogenidec, Boehringer, BMS, Celgene, CrescendoBio, EMD Serono, Hoffmann-La Roche, Italfarmaco, Janssen, MedImmune, Medac, Novartis, Novo Nordisk, Pfizer, Sanofi Aventis, Servier, Takeda, UCB Biosciences GmbH, Speakers bureau: AbbVie, Amgen, Alter, AstraZeneca, Baxalta Biosimilars, Biogenidec, Boehringer, BMS, Celgene, CrescendoBio, EMD Serono, Hoffmann-La Roche, Italfarmaco, Janssen, MedImmune, Medac, Novartis, Novo Nordisk, Pfizer, Sanofi Aventis, Servier, Takeda, UCB Biosciences GmbH, D. Lovell Grant/research support from: NIH, NIAMS, Consultant for: Astra-Zeneca, Bristol Meyers Squibb, AbbVie, Pfizer, Roche, Novartis, UBC, Forest Research Institute, Horizon, Johnson & Johnson, Biogen, Takeda, Genentech, GlaxoSmithKline, Boehringer Ingelheim, Celgene, Janssen, A. Ramanan Speakers bureau: Roche, AbbVie, R. Cuttica Consultant for: Roche, Novartis, Lilly, GlaxoSmithKline, Bristol-Myers Squibb, Janssen, Speakers bureau: Roche, Novartis, Lilly, GlaxoSmithKline, Bristol-Myers Squibb, Janssen, J. Weiss: None declared, M. Henrickson: None declared, H. Schmeling Grant/research support from: Janssen, Pfizer, UCB Biosciences GmbH, J. Anton Grant/research support from: Roche, K. Minden Grant/research support from: AbbVie, Pfizer, Roche, Speakers bureau: AbbVie, Pfizer, Roche, Genzyme, Pharm-Allergan, J. Hsu Employee of: Roche, K. Bharucha Employee of: Genentech, S. Wimalasundera Employee of: Roche Products Ltd., A. Kadva Employee of: Genentech, R. Upmanyu Employee of: Roche Products Ltd., N. Mallalieu Shareholder of: Roche, Employee of: Roche, A. Martini Consultant for: Abbvie, Boehringer, Celgene, CrescendoBio, Janssen, MedImmune, Novartis, NovoNordisk, Pfizer, Sanofi Aventis, Vertex, Servier, Speakers bureau: Abbvie, Boehringer, Celgene, CrescendoBio, Janssen, MedImmune, Novartis, NovoNordisk, Pfizer, Sanofi Aventis, Vertex, Servier, H. Brunner: None declared